Mental Health and Chronic Pain in the Elderly - Alnaimi, Izzeldeen Abdullah; Yamani, Ibrahim Abdul Jaleel; Alkhatib, Ahed J (Journal of Cultural Analysis and Social Change, 2025)
Chronic pain occurs frequently among older people and is often persistent and disabling in nature. This pain usually worsens with other chronic diseases (comorbidities), sensory impairment and depression. Changes in the brain associated with chronic pain can disturb communications between brain sites that regulate feelings and sensory perceptions. This increases the odds of developing mental disorders. Fussier diseases can cause extremely high discomfort which can eventually cause many more serious diseases in others. Mental health care is not integrated with chronic pain management. Every elderly individual should undergo routine screening for mental disorders, especially depression and anxiety. The use of geriatric psychiatry expertise is strongly advised. Antidepressants, when well-monitored, will not increase morbidity or mortality in older patients, say experts. Social isolation worsens depression, so communities are encouraged to engage with their elders through intergenerational activities. Caregivers can also be better trained. Training geared toward physical and social participation, along with family-centered education and counseling, may lower depressive symptoms and improve overall quality of life in the elderly with persistent pain.